2018
DOI: 10.1186/s12885-018-4499-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive equation of metastasis in patients with malignant ovarian epithelial tumors with the Ca-125 marker

Abstract: BackgroundCancer antigen (CA) 125 (CA-125) is used in ovarian cancer detection and monitoring, whose serum level has a positive correlation with tumor stage. The aim of this study was to obtain a prediction metastasis equation in a group of patients with ovarian cancer based on Ca-125.MethodsA 2-group comparative observational study was conducted at a single oncologic institution (SOLCA) in Cuenca-Ecuador. All patients who were diagnosed with ovarian cancer between January 1996 and December 2016 were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, recent studies report that the binding mesothelin to Ca125 plays a crucial role in metastasis creation via spreading ovarian cancer cells in the peritoneal cavity [ 54 , 55 ]. Numerous studies reported increased concentration of Ca125 in ovarian cancer patients enhances the motility and invasiveness of cancer cells that lead to metastasis related to metastasis creation and disease progression [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies report that the binding mesothelin to Ca125 plays a crucial role in metastasis creation via spreading ovarian cancer cells in the peritoneal cavity [ 54 , 55 ]. Numerous studies reported increased concentration of Ca125 in ovarian cancer patients enhances the motility and invasiveness of cancer cells that lead to metastasis related to metastasis creation and disease progression [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood markers to monitor ovarian cancers can be physiologically raised during pregnancy [1]. Abnormal level of CA125 is widely used in epithelial ovarian cancer detection and monitoring [9]. CA 125 is often elevated at 1st trimester and its level is low in maternal serum but high in the amniotic fluid in 2nd and 3rd trimester so it still has diagnosis value for 2nd and 3rd trimester [3].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that the levels of SCCA were also increased in other types of cancer, including breast cancer (5). Sugar chain antigen 125 (CA-125) was used for the diagnosis of ovarian carcinoma and its sensitivity was primarily based on the staging of ovarian malignancies (6). However, it has been reported that the expression levels of CA-125 were also elevated in other malignancies, including ~10.4% of benign ovarian tumors (7).…”
Section: Introductionmentioning
confidence: 99%